The Power of Blood: The Many Faces of Women's Monthly Menses in Jewish Law and Beyond - Laufer-Ukeles, Pamela (Columbia Journal of Gender and Law, 2021)
Menstruation has many faces. This Essay will discuss competing narratives relating to menstruation as portrayed in Jewish law and culture, and assess the implications of such narratives for modern legal systems. These narratives depict menstruation in all its contradictions — as taboo and power, as health and imperfection, and as reflecting biological difference but not inequality. Each narrative will be discussed from a textual, legal, communal and, occasionally, personal perspective, conveying different meanings that have different cultural impacts, modern applications and reflect different aspects of the quest for equality. Together, these narratives provide a holistic vision of womanhood that resists simplification. Acknowledging that not only women menstruate, in this Essay I refer to women as those who menstruate because this is the category associated with menstruation used in Jewish law and it is the complexity of womanhood revealed by Jewish law and culture that I address. These four faces of menstruation are not characterized as positive or negative in and of themselves; rather, I analyze them each on their own terms, discussing how they may impact women in both negative and positive ways. The variability of these narratives demonstrates the need for women to shape their own narratives around their bodies in order to empower themselves within their communities. Moreover, the multiplicity of faces that menstruation involves, and the different ways that femininity can therefore impact womanhood, counsels promoting menstrual justice in a variety of ways, and from a variety of perspectives, creatively empowering women by recognizing their individual complexity. In Jewish law, menstruation engenders impurity, authority, fertility, and biological difference, and each of these faces of womanhood will be discussed in turn.